Analisis Keefektifan Instagram Sebagai Media Kampanye Nasionalisme dan Feminisme di Kalangan Remaja - Suwarno Liang; Roma Sebet Manurung (Departement of Mathematics Education, 2023)
Currently, Instagram is widely used as a media campaign for nationalism and feminism. There are several feminists and nationalist figures in Indonesia who also actively use Instagram social media, namely Retno Marsudi and Susi Pudjiastuti. The purpose of this research is to analyze the effectiveness of Instagram as a media campaign for nationalism and feminism among teenagers in Batam City. This research is an interpretative qualitative research with Roland Barthes's semiotic analysis. Primary data sources were obtained from Instagram posts in the form of image snippets and image elements, captions and netizens, and comments contained in these Instagram posts. While secondary data obtained was from books, journals (online), and articles (online). Data collection in this study was obtained by using documentation techniques. The collected data were then analyzed by interpreting the two stages of sign from Roland Barthes' semiotic theory. The results of the study show that feminism in Indonesia is considered very minimal when compared to nationalism. There is a gap between women and men. This is due to the strong culture and beliefs of the Indonesian people who think that women should not exceed men in various aspects.